Saint At Tashguzar Or Jingakli Ota Cemetery - Meilikulova Umida (Academia One, 2024)
This article talks about the shrine of Jingakli father, located in the Guzor district of Kashkadarya region, and its place in the pilgrimage tourism of the Guzor district. Also, it is said that it is different from similar shrines located in the district and that it needs new scientific research
Keywords: Jingakli father; Tashguzar; cotton policy